How (not) to measure institutions - Stefan Voigt (Philipps-University Marburg, Faculty of Business Administration and Economics, 2009)
The statement institutions matter has become commonplace. A precondition for it to be supported by empirical evidence, is, however, that institutions are measurable. Glaeser et al. (2004) attacks many studies claiming to prove the relevance of institutions for economic development as being based on flawed measures of institutions, or not even on institutions at all. This paper shows that their criticism deserves to be taken seriously, but that it is somewhat overblown. Some of the difficulties in measuring institutions are described and some ways of measuring them are proposed.
Keywords: B41; C81; C82; H11; K00; O17; O43; O57; 330; Institutions; Institutions vs. Policies; Measurement; Formal vs. Informal Institutions